Feasibility, acceptability and efficacy of a text message-enhanced clinical exercise rehabilitation intervention for increasing 'whole-of-day' activity in people living with and beyond cancer - Sjaan R. Gomersall; Tina L. Skinner; Elisabeth Winkler; Genevieve N. Healy; Elizabeth Eakin; Brianna Fjeldsoe (BMC, 2019)
Abstract Background Exercise interventions are typically delivered to people with cancer and survivors via supervised clinical rehabilitation. However, motivating and maintaining activity changes outside of the clinic setting remains challenging. This study investigated the feasibility, acceptability and efficacy of an individually-tailored, text message-enhanced intervention that focused on increasing whole-of-day activity both during and beyond a 4-week, supervised clinical exercise rehabilitation program for people with cancer and survivors. Methods Participants (n = 36; mean ± SD age 64.8 ± 9.6 years; 44.1 ± 30.8 months since treatment) were randomized 1:1 to receive the text message-enhanced clinical exercise rehabilitation program, or the standard clinical exercise rehabilitation program alone. Activity was assessed at baseline, 4-weeks (end of the standard program) and 12-weeks (end of enhanced program) using both device (activPAL accelerometer; sitting, standing, light-stepping, moderate-stepping) and self-report [Multimedia Activity Recall for Children and Adults (MARCA); sedentary, light, moderate-to-vigorous physical activity (MVPA)] methods. The MARCA also assessed time use domains to provide context to activity changes. Changes and intervention effects were evaluated using linear mixed models, adjusting for baseline values and potential confounders. Results The study had high retention (86%) and participants reported high levels of satisfaction [4.3/5 (±0.8)] with the intervention. Over the first 4 weeks, MARCA-assessed MVPA increased [+ 53.2 (95%CI: 2.9, 103.5) min/d] between groups, favoring the text message-enhanced program, but there were no significant intervention effects on sedentary behavior. By 12 weeks, relative to the standard group, participants in the text message-enhanced group sat less [activPAL overall sitting: − 48.2 (− 89.9, − 5.6) min/16 h awake; MARCA: -80.1 (− 156.5, − 3.8) min/d] and were participating in more physical activity [activPAL light stepping: + 7.0 (0.4, 13.6: min/16 h awake; MARCA MVPA: + 67.3 (24.0, 110.6) min/d]. The time-use domains of Quiet Time [− 63.3 (− 110.5, − 16.0) min/d] and Screen Time [− 62.0 (− 109.7, − 14.2) min/d] differed significantly between groups. Conclusions Results demonstrate feasibility, acceptability and efficacy of a novel, text message-enhanced clinical exercise rehabilitation program to support changes in whole-of-day activity, including both physical activity and sedentary behavior. Changes were largely seen at 12-week follow-up, indicating potential for the intervention to result in continued improvement and maintenance of behavior change following a supervised exercise intervention. Trial registration This trial is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12616000641493; date registered 17/5/16).